Management of Major Injuries to the Bile Duct at a Hepatobiliary Specialty Referral Center. Issue 5 (May 2023) - Zendel, Alex; Kumar, Aman; Serrano, Pablo; de Oliveira, Guilherme C.; Button, Julia; Gebre, Betelhme; Gerber, David A.; Desai, Chirag S.
Introduction: Aim is to evaluate geographical and demographic factors influencing management of bile duct injuries occurring during cholecystectomy in a tertiary hepato-pancreato-biliary center in Southeast US. Methods: All referrals for biliary injuries during cholecystectomy, between Jan 2017 and December 2020 were included. Results: 19 patients were identified with a median age of 59 (47-65), average BMI of 30.3 (18-49), and the prevalence of diabetes mellitus, hypertension and cardiovascular disease of 11%, 47% and 16%, respectively. The average transfer distance was 76 miles (8-102) and median transfer time was 3 days (1-12). 16 (84%) had Strasberg E injury, with 4 (21%) having a concomitant vascular injury (3 - right hepatic artery, 1 - right portal vein). Two (10.5%) were managed non-operatively, immediate surgical repair was performed in 2 (10.5%) and 15 (78.9%) patients underwent a delayed repair with a median of 87 days (69-118) from injury to repair. Median operative time was 5 hours (4-7), blood loss was 150 mL (100-200) and hospital stay was 8 days (6-12). Discussion: Factors including distance between hospitals, delays in patient transfer due to bed availability and transportation, play a role in the decision-making towards delayed repair. The delayed repair has the benefit of medical optimization of our high-risk patients' population.